Effect of salinity on hydroxyapatite nanoparticles flooding in enhanced oil Recovery : A mechanistic study - Ngouangna, Eugene N.; Jaafar, Mohd Zaidi; Norddin, Mnam; Agi, Augustine; Yakasai, Faruk; Oseh, Jeffrey O.; Mamah, Stanley C.; Yahya, Muftahu N.; Al-Ani, Muhanad (American Chemical Society, 2023)
Fluid-fluid interactions can affect any enhanced oil recovery (EOR) method, including nanofluid (NF) brine-water flooding. Flooding with NFs changes wettability and lowers oil-water interfacial tension (IFT). Preparation and modification affect the nanoparticle (NP) performance. Hydroxyapatite (HAP) NPs in EOR are yet to be properly verified. HAP was synthesized in this study using co-precipitation and in situ surface functionalization with sodium dodecyl sulfate in order to investigate its impact on EOR processes at high temperatures and different salinities. The following techniques were employed, in that sequence, to verify its synthesis: transmission electron microscopy, zeta potential, thermogravimetric analysis, Fourier transform infrared spectroscopy, X-ray diffraction, particle size analysis, and energy-dispersive X-ray spectra. The outcomes showed the production of HAP, with the particles being evenly dispersed and stable in aqueous solution. The particles' surface charge increased from -5 to -27 mV when the pH was changed from 1 to 13. The HAP NFs at 0.1 wt % altered the wettability of sandstone core plugs from oil-wet at 111.7 to water-wet at 9.0 contact angles at salinity ranges of 5000 ppm to 30,000 ppm. Additionally, the IFT was reduced to 3 mN/m HAP with an incremental oil recovery of 17.9% of the initial oil in place. The HAP NF thus demonstrated excellent effectiveness in EOR through IFT reduction, wettability change, and oil displacement in both low and high salinity conditions.